Respuesta :
Answer:
n² -2n -4
Step-by-step explanation:
an² + bn + c
2a is 2 so a is 1
3a + b is 1 so with knowing a, b is -2
sum of a b and c is -5 so c is -4
Step-by-step explanation:
an = A×n² + B×n + C
a1 = -5 = A×1² + B×1 + C = A + B + C
a2 = -4 = A×2² + B×2 + C = 4A + 2B + C
a3 = -1 = A×3² + B×3 + C = 9A + 3B + C
a2 - a1 = -4 - -5 = 1 = 4A+2B+C-A-B-C = 3A + B
3A = 1 - B
A = (1 - B)/3
a3 - a2 = -1 - -4 = 3 = 9A+3B+C-4A-2B-C = 5A + B
3 = 5A + B = 5(1 - B)/3 + B
9 = 5(1 - B) + 3B = 5 - 5B + 3B = 5 - 2B
4 = -2B
B = -4/2 = -2
A = (1 - -2)/3 = (1 + 2)/3 = 3 / 3 = 1
-5 = A+B+C = 1 - 2 + C = -1 + C
-4 = C
so,
an = n² - 2n - 4